Drafting Legal and Profitable Business Contracts:Legal Aspects to be Aware of - Polontoh, Herry; Andrias, Maria Yeti; Gani, Najamuddin (Jurnal Hukum dan Keadilan, 2025)
Drafting legitimate and profitable business contracts is a crucial aspect in the business world. This article aims to analyze the legal aspects that must be considered in the preparation of a business contract in order to qualify it for validity and provide benefits to the parties. This study uses normative methods with a juridical approach, namely analyzing the applicable legislation, legal doctrine, and court decisions related to business contracts. The results showed that the validity of the contract is highly dependent on the fulfillment of the conditions in Article 1320 of the Civil Code, including the agreement of the parties, legal competence, clear object, and lawful cause. Non-fulfillment of such conditions may result in cancellation of the contract or be null and void. In addition, a profitable contract must observe the principle of fairness and balance between the rights and obligations of the parties in order to avoid potential disputes that could harm business continuity. Therefore, transparency in the preparation of contracts and effective dispute resolution mechanisms are important factors to ensure contracts are not only legally valid, but also support the stability and sustainability of the business.